Tantangan dan Solusi Orang Tua dalam Membangun Kecakapan Literasi Anak Usia Dini - Annisa Nuraisyah Annas; Imas Baguna; Firmansah Kobandaha; Stefany Putri Abdjul; Irham Aeril Mardiansyah Yusuf; Sriwahyuni Asipu (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
This research aims to identify and analyze various challenges and solutions for parents in building early childhood literacy skills. This research uses a literature study method obtained from various sources. The results of this study show that one of the challenges is that the lack of knowledge and understanding of literacy can be overcome by holding training or workshops for parents on how to support children's literacy by focusing on reading techniques, playing with words and introducing books from an early age. Another example is that time limitations and busyness can be overcome by creating a daily routine that involves short literacy activities such as reading together before bed or listening to audio stories by paying attention to the abilities of parents and early childhood skills.